Cost-effective flexibilisation of an 80 MWe retrofitted biomass power plants: Improved combustion control dynamics using virtual air flow sensors. (October 2020) - Blondeau, J.; Museur, T.; Demaude, O.; Allard, P.; Turoni, F.; Mertens, J.
Abstract: As they deliver dispatchable renewable energy, biomass power plants are expected to play a key role in the stability of the future electricity grids dominated by intermittent renewables. Large-scale, biomass-fired power plants are often retrofitted from coal-fired plants. Such a fuel modification combined with decreasing pollutant emission limits and higher requirements in terms of load flexibility can lead to a decrease of the maximum power delivered by the unit. The limiting factors are partly related to the control systems of those plants. In this paper, we present the results of the upgrading of an 80 MW e, retrofitted biomass power plant that was achieved by improving the dynamic control of the combustion process. Thanks to the addition of virtual air flow sensors in the control system and the re-design of the combustion control loops, the undesired effects of a recent 10 % power increase on NO x emissions were more than compensated. The accurate control of the local NO x production in the furnace resulted in a decrease of these emissions by 15 % with an increased stability. This study will help increasing the cost-effectiveness of such conversions, and facilitate the development of dispatchable, renewable power units able to contribute to the grid stability.